Witchcraft and witchcraft-related violence in AmaZizi chiefdom of kwaZangashe, Eastern Cape - Jong, Nanette de (HTS teologiese studies, 2022)
This article explores witchcraft-related violence against elderly women in the AmaZizi chiefdom of kwaZangashe in Eastern Cape, South Africa. The potential causes that have promoted such violence form the central subject of the study. The study includes a research design that combines questionnaires, focus groups and follow-on interviews. The findings have revealed a prevalence of witchcraft beliefs in the region and have pointed to elderly women as the likely victims of witchcraft violence. This has resulted in AmaZizi’s elderly women being socially isolated, verbally abused and at risk of physical violence and even murder. This study concludes with several interventions organised to combat future witchcraft-related violence and to support the elderly women in the chiefdom.Contribution: By giving voice to the lives and stories of a community of people rendered invisible in the wider public sphere, this article introduces accounts on witchcraft and healthcare that might otherwise have gone unarticulated.